2014
DOI: 10.1016/j.ypmed.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Patient and physician gender concordance in preventive care in university primary care settings

Abstract: Background: The proportion of female physicians working in primary care medicine has increased for several decades. Several studies have reported physician gender differences in preventive health care received by patients, especially for gender-specific preventive services. However, limited data exist on the role of patient and physician gender and gender concordance in the broad spectrum of preventive care. Therefore, we assessed the association between physician gender, patient-physician gender concordance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
2
16
0
1
Order By: Relevance
“…This is consistent with the results reported by Jerant and colleagues that women with female physicians were more likely to report up-to-date mammography (23). Another retrospective study conducted in 10,001 patients in Switzerland reported that female physicians provided significantly more preventive care services than male physicians to both female (66.7% vs. 63.6%) and male patients (73.4% vs. 70.7%) but found no evidence of gender concordance on cancer screening (35). However, that study did not include cervical cancer screening (using Pap tests) and was done in a university primary care setting where almost all patients were treated in the first instance by residents at the end of their postgraduate training.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results reported by Jerant and colleagues that women with female physicians were more likely to report up-to-date mammography (23). Another retrospective study conducted in 10,001 patients in Switzerland reported that female physicians provided significantly more preventive care services than male physicians to both female (66.7% vs. 63.6%) and male patients (73.4% vs. 70.7%) but found no evidence of gender concordance on cancer screening (35). However, that study did not include cervical cancer screening (using Pap tests) and was done in a university primary care setting where almost all patients were treated in the first instance by residents at the end of their postgraduate training.…”
Section: Discussionmentioning
confidence: 99%
“…They may have more interest in gynecological cancers because of a shared susceptibility to the disease (Woodward et al, 1996). Women physicians may have been generally socialized to focus more attention toward preventive care, with more communication with patients and longer visit duration (Woodward et al, 1996;Roter and Hall, 2004;Krähenmann-Müller et al, 2014). Differences in the perception of what is most important in the work of the physician may matter: one study carried out in Norwegian medical schools found that, for women physicians, work satisfaction was associated with perceived clinical skills whereas for male physicians it was associated with feeling well with their peers (Finset et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Secondary cardiovascular prevention (i.e., after a first cardiovascular event) is more frequent for men: their risk factors are monitored better than those of women. [8][9][10][11][12] Most cardiovascular events, however, occur in people without known cardiovascular disease (88% in France 13 ). To our knowledge, only one study has examined gender differences exclusively for primary prevention of cardiovascular diseases; it reported results that differed according to the preventative procedures considered.…”
Section: Introductionmentioning
confidence: 99%